2017
DOI: 10.1002/erv.2527
|View full text |Cite
|
Sign up to set email alerts
|

Examining Maternal Psychopathology, Family Functioning and Coping Skills in Childhood Obesity: A Case–Control Study

Abstract: The shared family environment is an important risk factor in the development of childhood obesity. This study aims to examine differences in maternal psychopathology, family functioning, expressed emotion and coping skills between families of a child with obesity and those with a normal-weight child. This case-control study consisted of 50 mothers with a child (age 8-12 years) with obesity (p ≥ 97) and a control group of 50 mothers of a child with normal weight (p < 85), matched for age, sex and socio-economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 45 publications
1
22
0
1
Order By: Relevance
“…However, the expected results regarding EE were not obtained in the ENTREN‐F group, as there were no improvements in CC or EOI. As this is an important aspect in the relatives of children with obesity (Blanco et al, ; Sepulveda et al, ), it is therefore necessary to modify this part of the content for the final programme, increasing the content intended for family communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expected results regarding EE were not obtained in the ENTREN‐F group, as there were no improvements in CC or EOI. As this is an important aspect in the relatives of children with obesity (Blanco et al, ; Sepulveda et al, ), it is therefore necessary to modify this part of the content for the final programme, increasing the content intended for family communication.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these psychological correlates, the structure and modelling of the family's eating habits appear to be clearly associated factors (Laessle, Uhl, & Lindel, ; Munsch et al, ; Zeller et al, ), as well as other possible factors such as family stress, which is understood as the presence of psychological problems or somatic illnesses in the parents or the stress associated to a socioeconomic disadvantage (Goodman & Whitaker, ; Hasler et al, ; Hemmingsson, ). In this direction, studies show that parents of children with obesity report a negative experience and exhibit behaviour patterns that may act as maintenance factors for the disorder, such as the presence of high expressed emotion (EE) and the alteration of quality of life (Blanco et al, ; Sepulveda et al, ). Even though all these factors may be maintaining the problem and are predictors of a better or worse prognosis in childhood obesity interventions, emotional and family variables tend to still not be included in this type of treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The three studies unsuitable for pooling reported equivocal results. 48,49,55 Of the nine studies that examined childhood obesity and its association with maternal depression or anxiety, one small cohort study (n = 160) estimated a positive association, 48 seven were equivocal [49][50][51][52][53][54][55] and one reported a negative effect. 56 Of the three studies that examined duration of maternal depressive disorder, two found an increased risk associated with cumulative exposure to depression, but not of exposure to periodic depression.…”
Section: Asthma (Eight Studies)mentioning
confidence: 99%
“…Mothers with depression, generally, do not provide adequate care to their children, affecting their level of responsiveness to the child 7 . This is reflected in less healthy eating habits and less control over television viewing time and other sedentary behaviors, with low stimulation of recreational activities that require direct maternal involvement 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a relationship between mothers' mental disorders and their children's nutritional status [10][11][12] ; in this sense, some research projects indicate that depressed women in the postnatal period tend to breastfeed for less time than recommended 13 and to have malnourished or obese children [8][9][10] . Due to the increasing rates of depressive and anxiety disorders, it becomes of great relevance the investigation of their consequences in parentchild relations, especially during childhood, period when the child's habits are formed.…”
Section: Introductionmentioning
confidence: 99%